Komunikasi Bisnis dalam Perspektif Islam di Rumah Sakit Muhammadiyah Bandung (Studi Pada Divisi Bimbingan Rohani Rumah Sakit Muhammadiyah Bandung Dalam Peningkatan Kualitas Pelayanan Pasien) - Nurfitriana Novitasari Iskandar (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2018)
Communication is one of the dimensions that affect the quality of services by providing information to customers. The hospital also needs to improve the quality of service in terms of communication. This research aimed to to describe and analyze business communication in Islamic perspective (study on the spiritual guidance division of Rumah Sakit Muhammadiyah Bandung in improving services quality). This research is descriptive qualitative research. This research collects data through interview, observation, and literature study. The results of this study indicate that one of the forms of communication is communication in spiritual guidance activities as commitment of Rumah Sakit Muhammadiyah Bandung as an Islamic hospital. And as a strategy for improving hospital services in Rumah Sakit Muhammadiyah Bndung Keywords: Public Relations, Corporate Social Responsibility, Corporate Image.